SDN based security solution for legislative email communications: Safe guarding communication - Rupasinghe, P.; Kulatunga, K.; Murray, Iain; Keseva, K. (2017)
Communication plays a major role in the day to day activities of the world. Communication can be a gesture, phone call or by e-mail. This why most of the governments pay more attention to communication patterns and what people communicate with each other. In modern day information technology plays a major role in private and public sector events. It's better to be having implement security in to the major aspects of these events, like encrypted commendation channels. Software Defined Network (SDN) based encryption solution will be a advantage to the organizations so that they do not need to invest more on deploying new physical servers and implement high end encryption techniques.